A potentiometric biosensor for the determination of valproic acid: Human blood-based study of an anti-epileptic drug - Ozbek, Oguz; Isildak, Omer; Isildak, Ibrahim (ELSEVIER, 2021)
A potentiometric poly (vinyl chloride) (PVC) membrane-based biosensor has been developed for the determination of the anti-epileptic drug valproic acid in human blood samples. The valpmate-selective biosensor worked well over a wide concentration range from 1.0 x 10(-6) to 1.0 x 10(-1) mol L-1 with Nernstian slope of 59.0 + 3.6 mV/decade. The biosensor exhibited a lower detection limit of 9.75 x 10(-7) mol L-1. The developed valproate-selective biosensor showed very good selectivity for anti-epileptic drugs such as carbamazepine, levetiracetam and phenytoin, and for some ions present in human blood. The biosensor displayed a fast response time of less than 10 s, good reusability and stability, and operated in the wide pH range of 4.0-11.0. The morphology of the developed PVC membrane biosensor was analyzed by scanning electron microscopy. Finally, the determination of valproic acid in human blood samples was carried out using the standard addition method with very high recoveries.
Keywords: Valproic acid; Epilepsy; Biosensor; Anti-epileptic; Potentiometry; ION-SELECTIVE ELECTRODES; SURFACE-CHARGE DENSITY; SODIUM VALPROATE; PVC MEMBRANE; SENSOR; PHARMACOKINETICS; CONSTRUCTION; METABOLITES; SERUM; Biotechnology & Applied Microbiology; Engineering